Limitations of cognitive control on emotional distraction – Congruency in the Color Stroop task does not modulate the Emotional Stroop effect. - Straub, Elisa Ruth; Schmidts, Constantin; Kunde, Wilfried; Zhang, Jinhui; Kiesel, Andrea; Dignath, David (Cognitive, Affective & Behavioral Neuroscience, 2022)
Emotional information receives prioritized processing over concurrent cognitive processes. This can lead to distraction if emotional information has to be ignored. In the cognitive domain, mechanisms have been described that allow control of (cognitive) distractions. However, whether similar cognitive control mechanisms also can attenuate emotional distraction is an active area of research. This study asked whether cognitive control (triggered in the Color Stroop task) attenuates emotional distraction in the Emotional Stroop task. Theoretical accounts of cognitive control, and the Emotional Stroop task alike, predict such an interaction for tasks that employ the same relevant (e.g., color-naming) and irrelevant (e.g., word-reading) dimension. In an alternating-runs design with Color and Emotional Stroop tasks changing from trial to trial, we analyzed the impact of proactive and reactive cognitive control on Emotional Stroop effects. Four experiments manipulated predictability of congruency and emotional stimuli. Overall, results showed congruency effects in Color Stroop tasks and Emotional Stroop effects. Moreover, we found a spillover of congruency effects and emotional distraction to the other task, indicating that processes specific to one task impacted to the other task. However, Bayesian analyses and a mini-meta-analysis across experiments weigh against the predicted interaction between cognitive control and emotional distraction. The results point out limitations of cognitive control to block off emotional distraction, questioning views that assume a close interaction between cognitive control and emotional processing.